Aortoiliac occlusive disease: open or endo? - a narrative review - Semião,Ana Carolina (2022)
Abstract Introduction: Aortoiliac occlusive disease (AIOD) can be treated using either open surgical revascularization (OSR) or endovascular revascularization (ER). Methods: A Medline search was performed in order to identify articles focused on the treatment of aortoiliac occlusive disease. Additional articles of scientific interest for the purpose of this non-systematic review were included by cross-referencing. Results: There are a few articles reporting direct results between both techniques based on retrospective or prospective single center or multicenter studies. In the majority of studies, primary patency is generally better for surgery in comparison to ER, but at a cost of more postoperative complications, with higher rates of respiratory failure and wound infection in the open group. On the other hand, endovascular recanalization is related to higher rates of limb ischemia/thrombosis, renal dysfunction and reinterventions. In the presence of femoral artery calcified disease, the hybrid approach should be considered. Conclusions: Endovascular treatment is a suitable alternative for extensive AIOD and can be accomplished in a less invasive manner, with most midterm outcomes comparable with open reconstruction. Surgery should be reserved for multilevel calcified disease and after endovascular failure.